Arabic validation of the incharge financial distress/financial well-being scale and the new single-item financial stress scale - El Zouki, Christian-Joseph; Chahine, Abdallah; Hallit, Rabih; Malaeb, Diana; El Khatib, Sami; Nehme, Antonio; Obeid, Sahar; Fekih-Romdhane, Feten; Hallit, Souheil (Frontiers in Public Health, 2025)
BackgroundThe current study aimed to investigate the factor structure, reliability, and validity of the Arabic adaptation of the InCharge Financial Distress/Financial Well-Being Scale, and to examine a newly developed single-item measure of financial stress, the Single-Item Financial Stress scale (SIFiS), in a sample of Lebanese adults.MethodsIn this cross-sectional study, 403 participants completed an Arabic-translated version of the IFDFW scale via an online survey. Confirmatory factor analysis (CFA) was used to validate the scale.ResultsA one-factor structure was supported by the analysis. Internal reliability was excellent, with very high omega and alpha coefficients for the IFDFW scale (ω = 0.95, α = 0.95). A significantly lower mean IFDFW score was found in males compared to females. On the other hand, no significant differences were found between males and females on the SIFiS scores. Greater financial burden was significantly associated with higher levels of depression, anxiety, and stress.ConclusionThe findings confirm that the Arabic versions of the IFDFW scale and the SIFiS are valid and reliable. Their use is therefore recommended in various settings among Arabic-speaking adults. These simple and straightforward measurement tools may improve cross-cultural studies on financial well-being.